Fonologija samoglasniških nizov v slovenščini - Jurgec, Peter (Slavistična revija, 2004)
Vowel sequences are series of two or more vowels. this area, which has been for Slovene previously poorly investigated, displays numeorus phonological (homorganic, i-like, schwalike sequences, etc.) as well as supra-phonological limitations. In Standard Slovene they only appear in word formations (particularly acronyms), loan words, and proper names, rarely in interjections. The phenomenon is more common in some dialects (loss of a consonant or its vocalization). The author analyzed a total of 5.244 words with vowel sequences (5.084 entries from SSJK, 160 acronyms from SP 2001). Vowel sequences in Slovene usually consist of two segments (> 99 %), are word-internal (= 95 %), single-stressed or non-stressed (= 50 %), mophonological and falling (= 50 %). All combinations of all vowel phonemes are realized, except for /reduced vowel/, which appears in initial position in acronyms only.
Keywords: fonologija; samoglasnik; samoglasniški niz; Slovene; slovenščina